Root dentine and endodontic instrumentation: cutting edge microscopic imaging - Atmeh, Amre R. (Interface Focus, 2016)
Cutting of the dental hard tissues is an integral part of restorative dentistry. Cutting of the root dentine is also needed in preparation prior to endodontic treatment, with significant commercial investment for the development of flexible cutting instruments based around nickel titanium (NiTi) alloys. This paper describes the evolution of endodontic cutting instruments, both in materials used, e.g. the transition from stainless steel to NiTi, and the design of the actual instruments themselves and their method of activation—by hand or motor driven. We have been examining tooth-cutting interactions microscopically for over 25 years using a variety of microscopic techniques; in particular, video-rate confocal microscopy. This has given a unique insight into how many of the procedures that we take for granted are achieved in clinical practice, by showing microscopic video images of the cutting as it occurs within the tooth. This technology has now been extended to allow imaging of the endodontic instrument and the root canal wall for the first time. We are able to image dentine distortion and crack propagation during endodontic filing of the root canal space. We are also able to visualize the often claimed, but seldom seen action of contemporary endodontic instruments.